Overexpression of NaV1.6 in the rostral ventrolateral medulla in rats mediates stress-induced hypertension via glutamate regulation. (17th February 2022) - Tong, Lei; Xing, Mengyu; Wu, Jiaxiang; Zhang, Shuai; Chu, Dechang; Zhang, Haili; Chen, Fuxue; Du, Dongshu
ABSTRACT: Background: The rostral ventrolateral medulla (RVLM) plays a key role in mediating the development of stress-induced hypertension (SIH). Furthermore, enhanced glutamate transport within glutamatergic neurons in the RVLM mediates pressor responses. Data from our previous studies suggest that the voltage-gated sodium channel NaV1.6 is overexpressed in neurons in the RVLM in SIH model rats and participates in the resulting elevation of blood pressure. However, previous studies have not investigated the relationship between NaV1.6 expression and glutamatergic neurons. Methods: Here, we constructed an SIH rat model by knocking down NaV1.6 via microinjection of clustered regularly interspaced short palindromic repeats (CRISPR) guide RNA into the RVLM. Glutamate-related markers were quantified by Western blotting and immunofluorescence, and blood pressure was measured in the rats. Results: Our findings showed that vesicular glutamate transporter 1 (VGluT1) protein expression in the RVLM was higher in SIH rats than in Control rats, and GAD67 protein expression in SIH rats was lower than that in Control rats. Therefore, the number of VGluT1-positive neurons increased, while the number of GAD67-labeled neurons decreased after stress. After knocking down NaV1.6 expression in the RVLM, VGluT1 expression and the number of VGluT1-positive neurons decreased relative to those in SIH rats, while GAD67 protein expression and the number of GAD67-labeled neurons increased relative to those in SIH rats. Conclusions: These results indicate that overexpression of NaV1.6 in the RVLM may mediate the transport and transformation of glutamate in neurons, and NaV1.6 may participate in SIH.